Forensic Medicine Education in Problem Based Learning: The Case of Pamukkale University - Zeybek, Volkan; Kurtuluş Dereli, Ayşe; Boz, Bora; Kara, Cüneyt Orhan; Acar, Kemalettin (The Bulletin of Legal Medicine, 2020)
As a result of health system and legal regulations in our country, primary care physicians have a great number of responsibilities related to forensic medicine services, but it is a known fact that our physicians describe forensic medicine as the most feared task because of the insufficiency of undergraduate forensic medical education.A horizontal and vertical integration, spiral structured training program is implemented at Pamukkale University Faculty of Medicine. While they learn the basic concepts in the first years, in the fifth grade they take active education methods through the two-week task. In this forensic medicine education, it will enable the students to develop their interest in forensic medicine and to achieve the objectives of gaining knowledge, skills and attitude in the core program. In this study, the undergraduate forensic medicine education model of … University Faculty of Medicine is presented in detail.
Keywords: forensic medicine education; task based learning; problem based learning